Solute partitioning in multi-component γ/γ′ Co–Ni-base superalloys with near-zero lattice misfit. (1st March 2016) - Meher, S.; Carroll, L.J.; Pollock, T.M.; Carroll, M.C.
Abstract: The addition of nickel to cobalt-base alloys enables alloys with a near zero γ − γ′ lattice misfit. The solute partitioning between ordered γ′ precipitates and the disordered γ matrix have been investigated using atom probe tomography. The unique shift in solute partitioning in these alloys, as compared to that in simpler Co-base alloys, derives from changes in site substitution of solutes as the relative amounts of Co and Ni change, highlighting new opportunities for the development of advanced tailored alloys. Graphical abstract: